Positive Solutions for Singular Complementary Lidstone Boundary Value Problems - Fanglei Wang; Yukun An (Abstract and Applied Analysis)
By using fixed-point theorems of a cone, we investigate the existence and multiplicity of positive solutions for complementary Lidstone boundary value problems: (−1)𝑛𝑢(2𝑛+1)(𝑡)=ℎ(𝑡)𝑓(𝑢(𝑡)), in 0<𝑡<1, 𝑢(0)=0, 𝑢(2𝑖+1)(0)=𝑢(2𝑖+1)(1)=0, 0≤𝑖≤𝑛−1, where 𝑛∈𝑁.